2011
DOI: 10.4236/ce.2011.24052
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measures of a Family-Based Education Approach with Mexican Immigrants in the Yakima Valley

Abstract: With the continued incidence of obesity and health related issues in the United States and especially in the Hispanic population, it is important to provide useful healthy lifestyle education to this population. One of the barriers to providing this information is the lack of culture sensitivity in the content and presentation of current programs. In this pilot study, pre and post tests were used to measure the effectiveness of Salsa, Sabor, y Salud, a culturally sensitive program designed for Latinos. Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…A previous study by Bennett et al regarding the SSS program found that there was an increase in servings of fruit and vegetables, but the increase was not significantly significant (2011). In comparing findings between this study and a previous one (Bennett et al, 2011), both studies had a significant increase in participants' knowledge that eating healthy foods increases energy. There was a significant decrease in milk servings in general for the previous study, but with this study there was an increase in lower fat milk products.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…A previous study by Bennett et al regarding the SSS program found that there was an increase in servings of fruit and vegetables, but the increase was not significantly significant (2011). In comparing findings between this study and a previous one (Bennett et al, 2011), both studies had a significant increase in participants' knowledge that eating healthy foods increases energy. There was a significant decrease in milk servings in general for the previous study, but with this study there was an increase in lower fat milk products.…”
Section: Discussionsupporting
confidence: 43%
“…One of the questionnaires, Salsa, Sabor y Salud Healthy Lifestyle Test, obtained from the National Latino Children's Institute (Bennett et al, 2011;Barrera et al, 2002), was used to assess knowledge, beliefs, and attitudes surrounding nutrition and physical activity. The other questionnaire, Washington State University (WSU) Food Behavior Checklist (Blackburn et al, 2006;Murphy, Kaiser, Townsend, & Allen, 2001;Townsend, Kaiser, Allen, Joy, & Murphy, 2003;Townsend, Sylva, Martin, Metz, & Wooten-Swanson, 2008), is a multiple choice questionnaire assessing food group preference, food frequency, food label knowledge, food security, and physical activity.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations